Electricity Generation by Shewanella decolorationis S12 without Cytochrome c - Yang, Yonggang; Kong, Guannan; Chen, Xingjuan; Lian, Yingli; Liu, Wenzong; Xu, Meiying (Frontiers in Microbiology, 2017)
Bacterial extracellular electron transfer (EET) plays a key role in various natural and engineering processes. Outer membrane c-type cytochromes (OMCs) are considered to be essential in bacterial EET. However, most bacteria do not have OMCs but have redox proteins other than OMCs in their extracellular polymeric substances of biofilms. We hypothesized that these extracellular non-cytochrome c proteins (ENCP) could contribute to EET, especially with the facilitation of electron mediators. This study compared the electrode respiring capacity of wild type Shewanella decolorationis S12 and an OMC-deficient mutant. Although the OMC-deficient mutant was incapable in direct electricity generation in normal cultivation, it regained electricity generation capacity (26% of the wide type) with the aid of extracellular electron mediator (riboflavin). Further bioelectrochemistry and X-ray photoelectron spectroscopy analysis suggested that the ENCP, such as proteins with Fe–S cluster, may participate in the falvin-mediated EET. The results highlighted an important and direct role of the ENCP, generated by either electricigens or other microbes, in natural microbial EET process with the facilitation of electron mediators.